The use of facebook as a propeller in the teaching/learning process of english as a second language with eighth graders at a public institution in Armenia, Quindio (2020)
Considering the multiple advantages and benefits offered by the use of different multimedia resources in all fields including education, there is a great deal of research that demonstrates the effectiveness of information and communication technologies (ICT’S) in teaching/learning processes, despite the fact that various studies can be found that support the use of ICT’s in education, there are still many teachers who continue to use traditional methods during their lessons, wasting the advantages of these multimedia resources, just as they do not take into account the knowledge that young people have about technology, since they have grown up in a digital age in which they can interact daily with different electronic devices. This research precisely evidences the problem that entails not using dynamic strategies in the English L2 methodology focused on oral production area.